1997
DOI: 10.4141/p96-113
|View full text |Cite
|
Sign up to set email alerts
|

Will low-glucosinolate cultivars of the mustards Brassica juncea and Sinapis alba be vulnerable to insect pests?

Abstract: Will low-glucosinolate cultivars of the mustards Brassica juncea and Sinapis alba be vulnerable to insect pests? Can J. Plant Sci. 77: 283-287. Foliar concentrations of the predominant glucosinolates in the mustards B. juncea (allyl glucosinolate, sinigrin) and S. alba (p-hydroxybenzyl glucosinolate, sinalbin) were determined in lines that had been selected in breeding programs for low levels of glucosinolates in their seeds for the oilseed market. The glucosinolate concentrations found in the cotyledons and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 14 publications
(25 reference statements)
2
26
1
1
Order By: Relevance
“…Sinigrin was used in this study as the basis of comparison between the visualized metabolic alterations. This could be related to the results obtained earlier by (29), where it was observed that the absence of sinigrin in plants did not alter the resistance response to the diamondback moth, suggesting that these results are consistent with those of (38). He reported that in Brassica, cultivars with low content of the glucosinolates sinigrin and sinalbin, showed no alteration in the susceptibility to Phyllotreta cruciferae and P. xylostella (specific to crucifers), despite noting a five-fold increase in susceptibility of these cultivars to Mamestra configurata (polyphagous insect).…”
Section: Biochemical Analysissupporting
confidence: 79%
“…Sinigrin was used in this study as the basis of comparison between the visualized metabolic alterations. This could be related to the results obtained earlier by (29), where it was observed that the absence of sinigrin in plants did not alter the resistance response to the diamondback moth, suggesting that these results are consistent with those of (38). He reported that in Brassica, cultivars with low content of the glucosinolates sinigrin and sinalbin, showed no alteration in the susceptibility to Phyllotreta cruciferae and P. xylostella (specific to crucifers), despite noting a five-fold increase in susceptibility of these cultivars to Mamestra configurata (polyphagous insect).…”
Section: Biochemical Analysissupporting
confidence: 79%
“…In other work with Brassica, seed glucosinolate concentrations have been shown to correlate with leaf glucosinolate concentrations and resistance to herbivory (Glen et al, 1990;Bodnaryk, 1997), however these lines represent extremely low levels of variation in glucosinolates compared with the levels in wild plants in the Brassicaceae, which are often orders of magnitude greater (Glen et al, 1990;Bodnaryk, 1997). Five seeds from each of the B. napus lines were planted in 500 ml pots in Pro-Mix soil (Red Hill, Pennsylvania).…”
Section: Manipulating Glucosinolate Concentrationmentioning
confidence: 99%
“…When the plant is dam aged and the cell integrity destroyed, the enzyme myrosinase catalyses the degradation of GLS to volatile molecules, mainly isothiocyanates (ITC) (Fahey et al, 2001). The latter are attrac tants and feeding stimulants for several crucifer specialist insects such as Phyllotreta cruciferae Goeze (Coleoptera: Chrysomelidae) and Plutella xylostella L. (Lepidoptera: Plutellidae) (Bodnaryk, 1997). Several Pieridae species such as Pieris rapae L. and P. napi oleracea Harris (Lepidoptera: Pieridae) also use GLS as oviposition stimulants (Huang & Renwick, 1994).…”
Section: Introductionmentioning
confidence: 99%